Stranger things. Six. #2 - Houser, Jody (Spotlight, 2020)
Six meets Three at Hawkins Lab and remembers him as her neighbor back home. She learns he was always a part of the program and is angry with him for lying to her. Meanwhile, Six voices her fear of the future and is encouraged to take her skills to the next level.